Implementasi Kebijakan Pendidikan Agama Islam di SDIT Al-Manar Pekanbaru: Implementasi kebijakan pendidikan - zaza, zazasalsabila (JURNAL ISLAMIKA, 2024)
This study aims to: determine the implementation of Islamic religious education policies, explain the supporting and inhibiting factors in the implementation of Islamic religious education policies, explain the impact of implementing Islamic religious education policies on students. This research is a field research using a qualitative approach, namely research aimed at describing and analyzing the conditions that exist in the field. Techniques that can be used to collect data by conducting interviews, observation and documentation based on the results of observations and research SD IT Al-manar have been good at implementing religious education policies. And the regulations for each school have religious practices and theories in carrying out the implementation of their religious education policies and the implementation of Islamic religious education policies here is carried out in a week. learned in theory before. There are several factors supporting the implementation of religious education at SD IT Al-manar, namely support from inside and outside the school with good cooperation between teachers and their parents. As well as there are additional classes that are also used in carrying out worship practices. And there are also several factors inhibiting the implementation of religious education at SD IT Al-manar, namely the existence of obstacles such as holidays which can sometimes hinder the learning process of Islamic religious education and also obstacles such as a lack of human resources. This study aims to: determine the implementation of Islamic religious education policies, explain the supporting and inhibiting factors in the implementation of Islamic religious education policies, explain the impact of implementing Islamic religious education policies on students. This research is a field research using a qualitative approach, namely research aimed at describing and analyzing the conditions that exist in the field. Techniques that can be used to collect data by conducting interviews, observation and documentation based on the results of observations and research SD IT Al-manar have been good at implementing religious education policies. And the regulations for each school have religious practices and theories in carrying out the implementation of their religious education policies and the implementation of Islamic religious education policies here is carried out in a week. learned in theory before. There are several factors supporting the implementation of religious education at SD IT Al-manar, namely support from inside and outside the school with good cooperation between teachers and their parents. As well as there are additional classes that are also used in carrying out worship practices. And there are also several factors inhibiting the implementation of religious education at SD IT Al-manar, namely the existence of obstacles such as holidays which can sometimes hinder the learning process of Islamic religious education and also obstacles such as a lack of human resources.